Side Effect of the Use of Acoustic Barriers Observed in the Infra Range - STANIEK, Andrzej Czesław; BARTMAŃSKI, Cezary (Archives of Acoustics, 2020)
Acoustic barriers which are positioned along traffic lanes are designed to protect the surroundings from excessive noise. Such structures are to reverberate, diffract and damp the propagating acoustic waves. However, this method of shielding has some disadvantages which include constraint visibility and structure-born noise. The interaction between traffic-caused movement of air mass and acoustic barriers may generate infra noise waves. That is undesirable and should be estimated. The authors undertook the research to diagnose the plausible side effect of structure-born noise of such barriers because it may influence human body (Kasprzak, 2014). As a mechanical structure, the acoustic barrier is characterized by mechanical parameters which, in the field of modal analysis, are made up of natural frequencies, damping factors and mode shapes. In this paper the authors investigated the acoustic pressure distribution in the neighborhood of a real acoustic barrier in the scope of infra noise propagation. The methods of modal analysis were used to identify natural frequencies of the barrier and dominating frequencies of propagating waves in the far field. The correlation between observed vibration and acoustic signals is presented.